A brown trout (Salmo trutta) population faces devastating consequences due to proliferative kidney disease and temperature increase: A case study from Austria. Issue 3 (17th December 2019) - Waldner, Karoline; Bechter, Thomas; Auer, Stefan; Borgwardt, Florian; El‐Matbouli, Mansour; Unfer, Günther
Abstract: Proliferative kidney disease (PKD) is an emerging parasitic disease that affects wild and farmed salmonid fishes worldwide. Currently, it is widespread in Europe with records in many countries. This study assessed the status of PKD in the river Wulka, a small Austrian river, which was known to host a vital brown trout population despite having high water temperatures. Contrary to the initial hypothesis that the river was free from PKD, we observed an overall PKD prevalence of 92%. Noninfected fish were restricted to the uppermost river section. Twenty‐two out of 87 PKD‐positive fish of all age classes showed clinical signs, while five individuals exhibited signs of recovering from PKD infection. The severity of clinical signs was significantly dependent on the fish length and age, with smaller or younger individuals being more severely affected. Comparison of data from the earlier fish sampling events with those results from 2017 and 2018, together with the analyses of the pattern of water temperature since 2010, indicates that Wulka's brown trout population might become extinct in the near future.